The Effects of Cooling Delay on the Cooling Response and the Physico-Chemical Properties of Eksotika Papaya - Salleh, Hanim (1997)
Handling papaya in bulk can result in cooling delay of up to forty-eight hours due to equipment, cost and labour factors. The effects of cooling delay on chilling injury, quality and storage life of papaya were studied to develop effective strategies in postharvest handling and storage. Sound fruits of maturity index 2 were stored at 26°C±2°C (control) and in the cool room (13°C±2°C) approximately 24, 48, 72 and 96 hours after harvest. Storage and fruits' temperature were monitored using data acquisition system to obtain cooling rates. Physico-chemical properties namely weight loss, moisture content, firmness, rupture force, colour, titratable acidity (TA), citric acid content, total soluble solids (TSS) and pH were recorded. Fruits were also access for chilling injury symptoms. Data were taken for fruits at ambient condition, room cooled fruits before (labelled as RCl, RC2, RC3 and RC4 for 1, 2, 3 and 4 days of cooling delay respectively) and after they have ripened (labelled as AF1, AF2, AF3 and AF4 for 1, 2, 3 and 4 days of cooling delay respectively) upon weekly removal from the cool room. Data were compared for significant differences. Longer cooling delay (RC3/AF3 and RC4/AF4) resulted in higher halfcooling time, higher weight loss, better colour development, higher TSS and lower in firmness and lower in chilling injury occurrences when compared to the shorter cooling delay (RCI/AFI and RC2/AF2). No good correlation were found for moisture content, rupture strength, pH, TA and citric acid content in relation to cooling delay. All treatments had acceptable quality up to the second week of storage for the cool room treatments, while the control had acceptable quality up to nine days. The results show that Eksotika papaya can tolerate up to ninety-six hours of cooling delay for a storage life of up to two weeks. This can help reduce the refrigeration cost.